2023
DOI: 10.1007/s12020-023-03326-6
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic tests for medullary thyroid carcinoma: an umbrella review

Abstract: Purpose To summarize the more robust evidence about the performance of tools useful for diagnosis of medullary thyroid carcinoma (MTC) such as calcitonin (Ctn) and other circulating markers, ultrasound (US), fine-needle aspiration (FNA), and other imaging procedures. Methods This systematic review of systematic reviews was carried out according to a predefined protocol. A search string was created. An electronical comprehensive search of literature was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
28
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 37 publications
0
28
0
1
Order By: Relevance
“…2 FNA cytology is an essential examination when thyroid cancer is suspected after US; however, just over half of MTC cases are identified in cytological samples. 2 Serum calcitonin is the most sensitive and accurate tool for detecting MTC, however, routine measurement is not universally accepted for all patients diagnosed with thyroid nodules. 3,4 Strong evidence supports measuring calcitonin in FNA washout fluids, with an estimated sensitivity at 98%, showing consistency across studies.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…2 FNA cytology is an essential examination when thyroid cancer is suspected after US; however, just over half of MTC cases are identified in cytological samples. 2 Serum calcitonin is the most sensitive and accurate tool for detecting MTC, however, routine measurement is not universally accepted for all patients diagnosed with thyroid nodules. 3,4 Strong evidence supports measuring calcitonin in FNA washout fluids, with an estimated sensitivity at 98%, showing consistency across studies.…”
mentioning
confidence: 99%
“…3,4 Strong evidence supports measuring calcitonin in FNA washout fluids, with an estimated sensitivity at 98%, showing consistency across studies. 2 Ogmen et al 1 found that routine measurement of calcitonin in serum, coupled with the search for calcitonin in FNA fluids in patients with elevated serum values, led to an earlier MTC diagnosis. Sensitivities of both serum and FNA calcitonin were significantly higher than those of cytology alone.…”
mentioning
confidence: 99%
See 3 more Smart Citations